THE ROLE OF THE BLUE OCEAN STRATEGY IN CREATING A NEW MARKET SPACE - A CASE STUDY OF A SIMPLE OF FOOD PRODUCTS MARKETING COMPANIES IN IRAQ - Osama Anmar Abdul Amir; Mohammed Edan Bani Al khazraje (Scholar Express Journals, 2023)
Traditional marketing strategies refer to the plans and situations that the company can take to establish itself in the market, or to increase its market share, while it is struggling with In order to achieve these goals, it is in constant conflict with competitors, the marketing strategy that this research draws attention to is the blue ocean strategy. In the modern business environment, competition has become intense, reaching the point of “blood fighting,” so the business environment has become like a red ocean, so the company that wants to succeed should leave the competition aside and find new markets (creating new demand) that is, go to the blue ocean, and this happens through innovation and value creation. This research is a scientific attempt to link between the blue ocean strategy and the company's market share, and this was applied to a sample of food marketing companies operating in Iraq. A random sample was selected from 7 companies specialized in marketing food products, and the questionnaire was used as a data collection tool, The number of measurable retrieved questionnaires reached 200. And used spss v.25 program to analyse the data. The researchers concluded that the rate of application of this strategy in Iraq is average, and that the companies that applied the blue ocean strategy had a positive impact on their market position.
Keywords: blue ocean strategy; creating a new market space; blue ocean and the red ocean.